PEMBACAAN ULANG TERHADAP WADHRIBUHUNNA DALAM SURAT AL-NISA’ AYAT 34 - Syarial Dedi (Universitas Islam Negeri Mataram, 2018)
Abstract: The classical scholars interpret wadhribuhunna (al-Nisa': 34) by hitting the wife as the last alternative after giving advice and separating the bed. Civilized blows are not barbaric by paying attention to the way and object of the blow. The modern muslim intellectuals criticize it from various perspectives; human rights, gender, equality between husband and wife in the household, psychology, and so on. Still they did not dare to move the meaning of wadhribuhunna from hitting. This research puts it down by threatening, scaring and not beating or scolding him. This meaning does not come out of the meaning of the dharaba language, and this meaning is also supported by the text and hikmah al-tasyri. This study is in the form of literature with content analysis method Abstrak: Ulama klasik mengartikan wadhribuhunna (al-Nisa’: 34)dengan memukul isteri sebagai alternatif terakhir setelah memberikan nasihat dan pisah ranjang. Pukulan beradab bukan biadab dengan memperhatikan cara dan obyek pukulan. Para intelektual muslim modern mengkritisi itu dari berbagai sudut pandang; hak azasi manusia, gender, kesetaraan suami-isteri dalam rumah tangga, psikologi, dan sebagainya. Tetap saja mereka tidak berani memindahkan makna wadhribuhunna dari memukul.Penelitian ini mena’wilkan wadhribuhunna dengan mengancam, menakut-nakuti dan tidak memukul atau memarahinya. Makna ini tidaklah keluar dari makna bahasa dharaba,dan makna ini juga didukung oleh nash serta hikmah al-tasyri’. Kajian ini berbentuk kepustakaan dengan metode content analysis (penalaran isi).